P149 Application of revised Pediatric Inflammatory Bowel Disease (PIBD) classes criteria to the Korean PIBD patients. (27th May 2021) - Shin, M; Lim, J G; Kim, M S; Moon, S Y; Hahn, J W; Kim, D H; Moon, J S; Ko, J S
Abstract: Background: In 2017, Porto group of ESPGHAN published the PIBD classes criteria, a diagnostic classification criteria for PIBD by conducting multi-center study, and the revised PIBD classes criteria were released in 2020 after multi-center verification. Consisting of 19 items classified into a total of 3 classes, this criteria classifies PIBD into UC, atypical UC, CD, and IBD-U through an algorithm. The purpose of this study is to examine the appropriateness of diagnosis and criteria by applying the revised PIBD classes-criteria for PIBD patients diagnosed in a certified tertiary hospital. Methods: Among 156 new patients aged 1–18 years old diagnosed with PIBD at Seoul National University Children's Hospital from January 1, 2014 to August 18, 2020, 102 patients who had no underlying disease, did not administer drugs that affect the immune system, whose key items of PIBD class criteria (upper and lower gastrointestinal endoscopy, gastrointestinal imaging, pathology, etc.) and basic demographic characteristics were verified were analyzed retrospectively through electronic medical records. Results: Of the 102 PIBD patients, 85 (83%) were initially diagnosed with CD, 15 (15%) with UC, and 2 (2%) with IBD-U by clinicians. Of the 102 patients, 69 (68%) were male, and the age of first diagnosis was 11.5±3.7 years. After applying the revised PIBD classes criteria, the diagnosis was changed to CD for 2 IBD-U patients, IBD-U for 7 UC patients, and CD for 1 UC patient. Finally, the diagnosis was changed to 86 (84%) CD, 8 (8%) UC and 7 (7%) IBD-U. The two patients whose diagnosis was changed from IBD-U to CD satisfied the items of Class 1, so the diagnosis was changed. All 7 patients whose diagnosis changed from UC to IBD-U did not satisfy all the items of Class 1, but most of the items 'Focal active colitis on histology in more than one biopsy' (6/7) and 'Focal enhanced gastritis on histology' (7/7) of class 3 criteria were satisfied, and the diagnosis has changed. Conclusion: As a result of applying the PIBD class criteria, there was no significant change in the diagnosis of CD, but the diagnosis of UC decreased by 73% and the diagnosis of IBD-U increased by 5 times. In this study group, the positive rates of items 'Fistulising disease', ''Thickened jejunal or ileal bowel loops on radiology or other evidence of significant small bowel inflammation on capsule endoscopy', 'Focal active colitis on histology in more than one biopsy' and 'Focal enhanced gastritis on histology' tended to be significantly higher than those of the previous study. So, Further validation and confirmation are needed.